Developing Cassava Based Frozen Products to Increase Housewife’s Income in Benda Baru Village, South Tangerang - Mutiara Dahlia; Cucu Cahyana (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Frozen snacks innovation is a food that is currently in trend and has a great opportunity to be developed.  Referring to the Jakarta State University community service program 2020-2024 it is directed at 4 (four)  focus activities, namely: Education; Public welfare; Art and culture; and Environment. Broadly speaking,  the implementation of the PKM program is community empowerment in preparing PKM plans for the  community in the form of product innovation originating from cassava tubers, thereby increasing culinary  productivity through optimizing cassava tubers and can increase household income generating. The aim is  to increase the community's ability to plan and manage the potential of cassava tubers as an effort to form  a group of people who are economically independent and prosperous. Another goal is to stimulate the  productivity of household culinary businesses that are widely cultivated by housewives in Benda Baru  village, South Tangerang, especially in the current state of the Covid-19 pandemic. The method used in this  activity is the provision of material, direct practice, and assistance in making frozen snack products, namely  french fries and cassava croquettes using cassava tubers as one of the variations of the local ingredients  used.